Foamed rubber composition, sponge and molded product

The foamed rubber composition, featuring sulfur-modified chloroprene rubber with specific functional groups and a controlled blowing agent, addresses the issues of low tear strength and shrinkage in chloroprene sponges, providing improved durability and appearance for applications like wetsuits.

JP7610954B2Active Publication Date: 2025-01-09DENKA CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020179389
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-10-27
Publication Date
2025-01-09
Estimated Expiration
2040-10-27

AI Technical Summary

Technical Problem

Chloroprene rubber sponges exhibit low tear strength and significant shrinkage, limiting their use in applications requiring high durability, such as wet suits.

Method used

A foamed rubber composition is developed by incorporating sulfur-modified chloroprene rubber with specific functional groups and a chemical blowing agent, optimizing the mass ratio of these groups and the blowing agent content to enhance tear strength and reduce shrinkage.

Benefits of technology

The composition results in a sponge with high tear strength, low shrinkage, and excellent appearance, suitable for products like wetsuits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007610954000001
    Figure 0007610954000001
  • Figure 0007610954000002
    Figure 0007610954000002
  • Figure 0007610954000003
    Figure 0007610954000003
Patent Text Reader

Abstract

To provide a sulfur-modified chloroprene rubber that can give a foam having high tear strength, a low shrinkage rate, and a good appearance.SOLUTION: A rubber foam composition contains a sulfur-modified chloroprene rubber 100 pts.mass and a chemical foamer 3-16 pts.mass. The sulfur-modified chloroprene rubber has a mercapto thiazole group A and a mercapto imidazole group B. The mass ratio of the content (B) of the functional group B to the content (A) of the functional group A, B / A, is 6.0 or less. The total content of the functional groups A and B is 0.10-0.60 pt.mass.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Background technology]

[0001] Taking advantage of its excellent dynamic properties, chloroprene rubber is used as a material for general industrial power transmission belts and conveyor belts, automotive air springs, anti-vibration rubber, etc. Chloroprene rubber can also be compounded with a foaming agent and heated to foam, to produce chloroprene rubber sponge, which is used in a variety of fields, such as automotive parts, the construction field, and leisure goods. Since chloroprene rubber sponge is a molded product having voids, it has problems with tear strength and shrinkage due to aging. For this reason, there has been a demand for the development of a chloroprene rubber sponge with high tear strength and low shrinkage.

[0002] Known means for obtaining chloroprene rubber sponge include a method of blending chloroprene rubber with an organic oxide, a foaming agent, a softener, a filler, and a reinforcing agent, and then heating and foaming the mixture (see, for example, Patent Document 1), and a method of blending chloroprene rubber with butadiene rubber, a softener, and a foaming agent, and then foaming the mixture by open vulcanization without pressure (see, for example, Patent Document 2). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2012-067235 A [Patent Document 2] Japanese Patent Application Publication No. 10-298328 Summary of the Invention [Problem to be solved by the invention]

[0004] The techniques described in Patent Documents 1 and 2 can obtain chloroprene rubber sponges with high expansion ratios. However, the obtained chloroprene rubber sponges have low tear strength. For this reason, there has been a demand for the development of a chloroprene rubber sponge that can be used in products that require high tear strength, such as wet suits.

[0005] An object of the present invention is to provide a foamed rubber composition which can provide a sponge having high tear strength and low shrinkage and excellent appearance, and a sponge and a molded article thereof. [Means for solving the problem]

[0006] As a result of intensive research to solve these problems, the inventors of the present application have completed a foamed rubber composition that, by introducing a specific structure into sulfur-modified chloroprene rubber and containing a specific foaming agent, can give molded articles with high tear strength, low shrinkage, and excellent appearance.

[0007] That is, in some aspects, the present invention provides the following [1] to

[15] . [1] A foamed rubber composition comprising: 100 parts by mass of a sulfur-modified chloroprene rubber having, at a molecular end, a functional group A represented by the following general formula (A) and a functional group B represented by the following general formula (B), wherein a mass ratio B / A of the content (A) of the functional group A to the content (B) of the functional group B is 6.0 or less, and the total content of the functional group A and the functional group B is 0.10 to 0.60 parts by mass; and 3 to 16 parts by mass of a chemical foaming agent. [ka] (In the formula, R1 and R2 each independently represent a hydrogen atom, a halogen atom, a hydroxy group, a cyano group, an alkyl group which may have a substituent, or an arylthio group which may have a substituent, and R1 and R2 may be bonded to each other to form a ring which may have a substituent.) [ka] (In the formula, R3 and R4 each independently represent a hydrogen atom, a halogen atom, a hydroxyl group, a cyano group, an alkyl group which may have a substituent, or an arylthio group which may have a substituent, and R3 and R4 may be bonded to each other to form a ring which may have a substituent.) [2] The foamed rubber composition according to [1], wherein the mass ratio B / A is greater than 0 and is not greater than 6.0. [3] The foamed rubber composition according to [1] or [2], wherein the functional group A has a benzothiazole ring formed by R1 and R2 bonding to each other. [4] The functional group B wherein R3 and R4 are bonded to each other to form a benzimidazole ring. [5] The foamed rubber composition according to any one of [1] to [4], containing 0.05 to 0.40 parts by mass of the functional group A per 100 parts by mass of the sulfur-modified chloroprene. [6] The foamed rubber composition according to any one of [1] to [5], wherein the content of the functional group B is 0.05 to 0.40 parts by mass per 100 parts by mass of the sulfur-modified chloroprene. [7] The foamed rubber composition according to any one of [1] to [6], containing 0.0005 to 0.01 parts by mass of thiazole per 100 parts by mass of the sulfur-modified chloroprene rubber. [8] The thiazole is N-cyclohexyl-2-benzothiazole sulfenamide, N-cyclohexyl-4-methyl-2-benzothiazole sulfenamide, N-cyclohexyl-4,5-dimethyl-2-benzothiazole sulfenamide, N,N-dicyclohexyl-1,3-benzothiazole-2-sulfenamide, N-(tert-butyl)-2-benzothiazole sulfenamide, N,N-diisopropyl-2-benzothiazole sulfenamide, 4,5-dihydroxy ...-cyclohexyl-4,5-dimethyl-2-benzothiazole sulfenamide, N-cyclohexyl-4,5-dimethyl-2-benzothiazole sulfenamide, N-cyclohexyl-4,5-dimethyl-2-benzothiazole sulfenamide, N-cyclohexyl-4,5-dimethyl-2-benzothiazole sulfenamide The foamed rubber composition according to [7], wherein the compound is at least one compound selected from the group consisting of thiazole-2-sulfenamide, N-cyclohexyl-4,5-dihydrothiazole-2-sulfenamide, N-oxydiethylbenzothiazole-2-sulfenamide, 2-(4'-morpholinyldithio)benzothiazole, 2-mercaptobenzothiazole, 4,5-dihydro-2-mercaptothiazole, dibenzylthiazolyl disulfide, and 2-(morpholinodithio)benzothiazole. [9] The foamed rubber composition according to any one of [1] to [8], containing 0.005 to 0.2 parts by mass of an imidazole per 100 parts by mass of the sulfur-modified chloroprene rubber.

[10] The foamed rubber composition according to [9], wherein the imidazoles are at least one compound selected from the group consisting of 2-mercaptoimidazole, 2-mercaptobenzimidazole, N-cyclohexyl-1H-benzimidazole-2-sulfenamide, 2-methoxycarbonylamino-benzimidazole, 2-mercaptomethylbenzimidazole, 2-mercapto-5-methoxybenzimidazole, 2-mercapto-5-carboxybenzimidazole, sodium 2-mercaptobenzimidazole-5-sulfonate dihydrate, 2-mercapto-5-nitrobenzimidazole, and 2-mercapto-5-aminobenzimidazole.

[11] The foamed rubber composition according to [9] or

[10] , wherein a mass ratio D / C of a content D of the imidazoles to a content C of the thiazole is 0 to 200.

[12] The foamed rubber composition according to any one of [1] to

[11] , wherein the sulfur-modified chloroprene rubber has a Mooney viscosity of 20 to 80.

[13] The foamed rubber composition according to any one of [1] to

[12] , wherein the chemical foaming agent is at least one selected from the group consisting of an azo compound, a nitroso compound, a sulfonyl hydrazide compound, an azide compound and an inorganic foaming agent.

[14] A sponge made of the foamed rubber composition according to any one of [1] to

[13] .

[15] A molded article made of the sponge described in

[14] . Effect of the Invention

[0008] According to the present invention, a foamed rubber composition capable of producing a sponge having high tear strength and low shrinkage and excellent appearance, a sponge, and a molded article are obtained. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] A preferred embodiment for carrying out the present invention will be described below. Note that the embodiment described below is an example of a typical embodiment of the present invention, and the scope of the present invention is not to be interpreted narrowly by this embodiment.

[0010] The foamed rubber composition of the present invention contains 100 parts by mass of a sulfur-modified chloroprene rubber having a functional group A represented by the following general formula (A) and a functional group B represented by the following general formula (B) at a molecular end, wherein the mass ratio B / A of the content (A) of the functional group A to the content (B) of the functional group B is 6.0 or less, and the total content of the functional group A and the functional group B is 0.10 to 0.60 parts by mass, and 3 to 16 parts by mass of a chemical foaming agent. [ka] (In the formula, R1 and R2 each independently represent a hydrogen atom, a halogen atom, a hydroxy group, a cyano group, an alkyl group which may have a substituent, or an arylthio group which may have a substituent, and R1 and R2 may be bonded to each other to form a ring which may have a substituent.) [ka] (In the formula, R3 and R4 each independently represent a hydrogen atom, a halogen atom, a hydroxyl group, a cyano group, an alkyl group which may have a substituent, or an arylthio group which may have a substituent, and R3 and R4 may be bonded to each other to form a ring which may have a substituent.)

[0011] <Sulfur-modified chloroprene rubber> The sulfur-modified chloroprene rubber includes a latex obtained by emulsion-polymerizing 2-chloro-1,3-butadiene (hereinafter also referred to as "chloroprene") alone or chloroprene with other monomers in the presence of sulfur to introduce sulfur into the main chain, and adjusting the molecular weight of the sulfur-modified chloroprene polymer using thiazole, and a sulfur-modified chloroprene rubber obtained by drying and washing the latex by a general method. The production process of the sulfur-modified chloroprene rubber will be described in detail below.

[0012] <Polymerization process> The sulfur-modified chloroprene rubber is prepared by emulsion polymerization of chloroprene, sulfur, and, if necessary, a monomer copolymerizable with chloroprene to obtain a polymerization liquid.

[0013] Examples of monomers copolymerizable with chloroprene include 2,3-dichloro-1,3-butadiene, 1-chloro-1,3-butadiene, styrene, acrylonitrile, methacrylonitrile, isoprene, butadiene, and methacrylic acid and their esters, and two or more of them can be used in combination. When using these monomers, it is preferable to use them within a range that does not impair the properties of the resulting sulfur-modified chloroprene rubber, and it is preferable to use them in an amount of 10 mass% or less of the total monomers including chloroprene. If the amount of these monomers used exceeds 10 mass%, the processability of the resulting sulfur-modified chloroprene rubber may decrease.

[0014] Among these monomers, for example, the use of 2,3-dichloro-1,3-butadiene can slow down the crystallization rate of the resulting sulfur-modified chloroprene rubber. The sulfur-modified chloroprene rubber having a slow crystallization rate can maintain rubber elasticity even in a low-temperature environment, and can improve, for example, the low-temperature compression set.

[0015] In emulsion polymerization, the amount of sulfur (S8) added is preferably 0.01 to 0.6 parts by mass, more preferably 0.1 to 0.5 parts by mass, based on 100 parts by mass of the total of the monomers to be polymerized. If the amount of sulfur (S8) is less than 0.01 parts by mass, the mechanical properties and dynamic properties of the resulting sulfur-modified chloroprene rubber may not be obtained. On the other hand, if the amount of sulfur (S8) exceeds 0.6 parts by mass, the adhesiveness of the resulting sulfur-modified chloroprene rubber to metals may become too strong, making it impossible to process.

[0016] As the emulsifier used in the emulsion polymerization, one or more of known emulsifiers or fatty acids that can be used in the emulsion polymerization of chloroprene can be freely selected and used. Specific examples of the emulsifier include rosin acids, metal salts of aromatic sulfonic acid-formaldehyde condensates, sodium dodecylbenzenesulfonate, potassium dodecylbenzenesulfonate, sodium alkyldiphenylethersulfonate, potassium alkyldiphenylethersulfonate, sodium polyoxyethylene alkylethersulfonate, sodium polyoxypropylene alkylethersulfonate, potassium polyoxyethylene alkylethersulfonate, and potassium polyoxypropylene alkylethersulfonate. Among these, it is particularly preferable to use rosin acids. Here, the rosin acids refer to rosin acid or disproportionated rosin acid, or alkali metal salts of disproportionated rosin acid, or compounds thereof. A suitable emulsifier is an aqueous alkali soap solution consisting of a mixture of an alkali metal salt of disproportionated rosin acid and a saturated or unsaturated fatty acid having 6 to 22 carbon atoms. Constituents of disproportionated rosin acid include, for example, sesquiterpene, 8,5-isopimaric acid, dihydropimaric acid, secodehydroabietic acid, dihydroabietic acid, deisopropyldehydroabietic acid, and demethyldehydroabietic acid.

[0017] The pH of the emulsion at the start of emulsion polymerization is desirably 10.5 or more. Here, the emulsion is a mixed liquid of chloroprene, a monomer copolymerizable with chloroprene, an emulsifier, sulfur (S8), etc., immediately before the start of emulsion polymerization. This also includes cases where the composition is changed by the post-addition or divided addition of these monomers and sulfur (S8). By setting the pH at 10.5 or more, when rosin acids are used as emulsifiers, it is possible to prevent polymer precipitation during polymerization and control the polymerization stably. The pH of the emulsion can be adjusted by the amount of an alkali component such as sodium hydroxide or potassium hydroxide present during emulsion polymerization.

[0018] The polymerization temperature for the emulsion polymerization is from 0 to 55°C, preferably from 30 to 55°C, from the viewpoints of polymerization controllability and productivity.

[0019] As the polymerization initiator, potassium persulfate, benzoyl peroxide, ammonium persulfate, hydrogen peroxide, etc., which are used in normal radical polymerization, can be used. The polymerization is carried out to a polymerization rate of 60 to 95%, preferably 70 to 90%, and then the polymerization is terminated by adding a polymerization terminator.

[0020] From the viewpoint of productivity, the polymerization rate is preferably 60% or more. From the viewpoint of suppressing the development of a branched structure and the generation of gel, which affect the processability of the obtained sulfur-modified chloroprene rubber, the polymerization rate is preferably 95% or less. Examples of polymerization terminators for the polymer include thiodiphenylamine, 4-tert-butylcatechol, and 2,2'-methylenebis-4-methyl-6-tert-butylphenol. The polymerization terminators may be used alone or in combination of two or more.

[0021] <Molecular weight adjustment process> The molecular weight adjusting step is a step of adding thiazole to the polymerization liquid obtained in the polymerization step, and reacting the polysulfide bonds (S2 to S8) present in the main chain of the sulfur-modified chloroprene polymer in the polymerization liquid with the added thiazole to form functional group A represented by the general formula (A) derived from the added thiazole, while cleaving and depolymerizing the sulfur-modified chloroprene polymer. Hereinafter, the chemical used for cleaving and depolymerizing the sulfur-modified chloroprene polymer is referred to as a molecular weight adjusting agent.

[0022] The type of thiazole to be added may be one or more of known thiazoles. In the present invention, N-cyclohexyl-2-benzothiazole sulfenamide, N-cyclohexyl-4-methyl-2-benzothiazole sulfenamide, N-cyclohexyl-4,5-dimethyl-2-benzothiazole sulfenamide, N,N-dicyclohexyl-1,3-benzothiazole-2-sulfenamide, N-(tert-butyl)-2-benzothiazole sulfenamide, N,N-diisopropyl-2-benzothiazole sulfenamide, 4,5- It is preferable that the compound is at least one compound selected from dihydrothiazole-2-sulfenamide, N-cyclohexyl-4,5-dihydrothiazole-2-sulfenamide, N-oxydiethylbenzothiazole-2-sulfenamide, 2-(4'-morpholinyldithio)benzothiazole, 2-mercaptobenzothiazole, 4,5-dihydro-2-mercaptothiazole, dibenzylthiazolyl disulfide, and 2-(morpholinodithio)benzothiazole.

[0023] The amount of thiazole added is preferably 0.2 to 3 parts by mass relative to 100 parts by mass of the sulfur-modified chloroprene polymer in the polymerization liquid. By making the amount of thiazole added 0.2 parts by mass or more, the tear strength is improved, the shrinkage rate is reduced, and a molded product with excellent appearance is obtained. In addition, by making the amount of thiazole added 3 parts by mass or less, a sulfur-modified chloroprene rubber with an appropriate Mooney viscosity can be obtained, and as a result, the vulcanization moldability can be improved.

[0024] In the molecular weight adjustment process, imidazoles can be used in combination as molecular weight adjusters. In the polymerization solution, imidazoles react with thiazole to form a reactant that is more reactive with polysulfide bonds than thiazoles or imidazoles, making it easier to adjust the Mooney viscosity. The reactant reacts with the polysulfide bonds of the sulfur-modified chloroprene polymer to form functional group A and functional group B represented by the general formula (B) derived from the added imidazoles. The imidazole to be added may be one or more of known imidazoles. In particular, it is preferable to use at least one compound selected from 2-mercaptoimidazole, 2-mercaptobenzimidazole, N-cyclohexyl-1H-benzimidazole-2-sulfenamide, 2-methoxycarbonylamino-benzimidazole, 2-mercaptomethylbenzimidazole, 2-mercapto-5-methoxybenzimidazole, 2-mercapto-5-carboxybenzimidazole, sodium 2-mercaptobenzimidazole-5-sulfonate dihydrate, 2-mercapto-5-nitrobenzimidazole, and 2-mercapto-5-aminobenzimidazole.

[0025] When an imidazole is used, the amount of the imidazole added is not particularly limited, but is preferably 0.2 to 3 parts by mass, more preferably 0.5 to 1.2 parts by mass, per 100 parts by mass of the polymer in the polymerization liquid. By setting the amount of the imidazole added within this range, it becomes easier to control the Mooney viscosity of the raw rubber, the tear strength is improved, and a molded product with excellent appearance can be obtained.

[0026] The polymer latex that has been subjected to the molecular weight adjustment step is cooled, pH adjusted, frozen, dried, etc., by a general method to obtain a sulfur-modified chloroprene rubber. The obtained sulfur-modified chloroprene rubber is characterized by containing 0.05 to 0.40 parts by mass of functional group A represented by the general formula (A) per 100 parts by mass. The content of functional group A can be adjusted by adjusting the amount of thiazole added in the molecular weight adjustment step or the treatment time and treatment temperature in the molecular weight adjustment step. By setting the content of functional group A within the above range, tear strength is improved, shrinkage rate is reduced, and a molded product with excellent appearance can be obtained.

[0027] The obtained sulfur-modified chloroprene rubber has 0.0005 to 0.01 parts by mass of unreacted thiazole remaining per 100 parts by mass of the rubber, which improves the tear strength of the molded product and contributes to reducing the shrinkage rate. The amount of unreacted thiazole remaining can be adjusted by adjusting the amount of thiazole added in the molecular weight adjustment step and the treatment time and treatment temperature in the molecular weight adjustment step.

[0028] In the case where imidazoles are used in the molecular weight adjustment step, the content of the functional group B represented by the general formula (B) present in the obtained sulfur-modified chloroprene rubber is not particularly limited. For example, in the case where 0.2 to 3 parts by mass of imidazoles are added to 100 parts by mass of the polymer in the polymerization liquid in the molecular weight adjustment step, the obtained raw rubber (composition (2)) contains 0.05 to 0.40 parts by mass of the functional group B and 0.005 to 0.2 parts by mass of unreacted imidazoles to 100 parts by mass of the sulfur-modified chloroprene rubber. The content of the functional group B and the amount of unreacted imidazoles can be adjusted by adjusting the amount of imidazoles added and the treatment time and treatment temperature of the molecular weight adjustment step. By setting the content of the functional group B within the above range, the tear strength is improved and a molded product with excellent appearance can be obtained.

[0029] The mass ratio (B / A) of the content of functional group A to the content of functional group B is 6.0 or less, and preferably more than 0 and 6.0 or less. The total mass (A+B) of the contents of functional group A and functional group B is 0.10 to 0.60 parts by mass. By setting the mass ratio (B / A) within this range, a molded article with excellent shrinkage can be obtained. If the total mass (A+B) is less than 0.1 parts by mass, the shrinkage rate increases and a molded article with excellent appearance cannot be obtained. If the total mass (A+B) exceeds 0.6 parts by mass, the Mooney viscosity of the sulfur-modified chloroprene rubber obtained drops significantly, making it impractical.

[0030] The contents of functional group A and functional group B in the sulfur-modified chloroprene rubber can be quantified by the following procedure. The obtained sulfur-modified chloroprene rubber is purified with benzene and methanol, and freeze-dried again to obtain a measurement sample. The obtained measurement sample is subjected to 1H-NMR measurement in accordance with JIS K-6239. The obtained measurement data is corrected based on the peak (7.24 ppm) of chloroform in deuterated chloroform used as a solvent, and the areas of the peaks having peak tops at 7.72 to 7.83 ppm and 6.99 to 7.23 ppm are calculated based on the corrected measurement data.

[0031] Furthermore, the ratio (D / C) of the thiazole (C) to the imidazole content (D) is preferably 0 to 2000. By setting the content ratio (D / C) within this range, the physical property balance of the tear strength and shrinkage rate of the obtained molded article becomes more favorable.

[0032] The content of unreacted thiazole (C) and the content of unreacted imidazoles (D) in the sulfur-modified chloroprene rubber can be quantified by the following procedure. 1.5g of the obtained sulfur-modified chloroprene rubber is dissolved in 30ml of benzene, and then 60ml of methanol is added dropwise to precipitate the rubber component and separate it from the solvent, and the non-rubber component is collected as a solvent-soluble component. The precipitated polymer is dissolved in benzene and methanol is added dropwise again in the same manner to separate the rubber component and similarly collect the non-rubber component as a solvent-soluble component. The first and second solvents are mixed to a constant volume of 200ml, and this is used as the measurement sample. 20μL of the measurement sample is injected into a liquid chromatograph (LC Hitachi, Pump: L-6200, L-600 UV detector: L-4250). The LC mobile phase is used with varying ratios of acetonitrile and water, and is run at a flow rate of 1ml / min. The column used is an Inertsil ODS-3 (φ4.6×150mm 5μm GL Science). The peak detection time of thiazole and imidazoles (measurement wavelength: 300 nm) is confirmed with a standard solution, and the quantitative value is calculated from the calibration curve obtained from the peak area. The amount of unreacted thiazole and unreacted imidazoles in the sulfur-modified chloroprene rubber is calculated by comparing this quantitative value with the amount of sample used in the analysis.

[0033] The Mooney viscosity of the sulfur-modified chloroprene rubber is not particularly limited, but is preferably adjusted to a range of 20 to 80. By adjusting the Mooney viscosity of the sulfur-modified chloroprene rubber to this range, the processability of the obtained sulfur-modified chloroprene rubber can be maintained. The Mooney viscosity of the sulfur-modified chloroprene rubber can be adjusted by adjusting the amount of molecular weight modifier added and the treatment time and treatment temperature in the molecular weight adjustment step.

[0034] The sulfur-modified chloroprene rubber may contain a small amount of stabilizer to prevent a change in Mooney viscosity during storage. The type of stabilizer that can be used in the present invention may be freely selected from one or more known stabilizers that can be used in chloroprene rubber. Examples of such stabilizers include phenyl-α-naphthylamine, octylated diphenylamine, 2,6-di-tert-butyl-4-phenylphenol, 2,2'-methylenebis(4-methyl-6-tert-butylphenol), and 4,4'-thiobis-(6-tert-butyl-3-methylphenol). Among these stabilizers, 4,4'-thiobis-(6-tert-butyl-3-methylphenol) is preferred.

[0035] <Chemical foaming agent> The chemical foaming agent may be either a chemical foaming agent or an inorganic foaming agent. Examples of the chemical foaming agent include azo compounds, nitroso compounds, sulfonyl hydrazide compounds, azide compounds, and carbondiamide compounds. More preferably, sulfonyl hydrazide compounds and azo compounds are used.

[0036] The chemical foaming agent used has a decomposition temperature of preferably 120° C. to 200° C., more preferably 130° C. to 170° C. By setting the decomposition temperature of the chemical foaming agent within this range, it becomes easy to control chemical foaming and vulcanization, the shrinkage rate is reduced, and a molded product with excellent appearance can be obtained.

[0037] The amount of the chemical foaming agent added is 3 to 20 parts by mass based on 100 parts by mass of the sulfur-modified chloroprene rubber. If the amount of the chemical foaming agent is less than 3 parts by mass, the amount of the foaming agent is insufficient, and a sufficient amount of decomposition gas cannot be obtained to obtain a foam. If the amount of the chemical foaming agent exceeds 20 parts by mass, it is difficult to achieve a balance between foaming and vulcanization, and the appearance and tear strength of the obtained molded product may be inferior.

[0038] <Sponge> The sulfur-modified chloroprene rubber to which a chemical foaming agent has been added can be made into a sponge by mixing it with a metal compound, a plasticizer, a filler, etc. using a roll, a Banbury mixer, an extruder, etc., and then adding a foaming agent and vulcanizing it while foaming.

[0039] The metal compound is added to adjust the vulcanization rate of the sulfur-modified chloroprene rubber and to adsorb chlorine sources such as hydrogen chloride generated by the dehydrochlorination reaction of the sulfur-modified chloroprene rubber, thereby suppressing deterioration of the sulfur-modified chloroprene rubber. As the metal compound, for example, oxides or hydroxides of zinc, titanium, magnesium, lead, iron, beryllium, calcium, barium, germanium, zirconium, vanadium, molybdenum, tungsten, etc. can be used. These metal compounds may be used alone or in combination of two or more.

[0040] The amount of the metal compound added is not particularly limited, but is preferably in the range of 3 to 15 parts by mass per 100 parts by mass of the sulfur-modified chloroprene rubber. By adjusting the amount of the metal compound added within this range, the mechanical strength of the obtained molded article can be improved.

[0041] The plasticizer is added to reduce the hardness of the sulfur-modified chloroprene rubber and improve its low-temperature properties. In addition, when the sulfur-modified chloroprene rubber is used to manufacture a sponge, the plasticizer can improve the texture of the sponge. Examples of the plasticizer include dioctyl phthalate, dioctyl adipate {bis(2-ethylhexyl) adipate}, white oil, silicone oil, naphthene oil, aromatic oil, triphenyl phosphate, and tricresyl phosphate. These plasticizers may be used alone or in combination of two or more.

[0042] The amount of the plasticizer to be added is not particularly limited, but is preferably in the range of 50 parts by mass or less per 100 parts by mass of the sulfur-modified chloroprene rubber. By adjusting the amount of the plasticizer to be added within this range, the tear strength of the obtained molded article can be maintained while the above-mentioned effects can be exhibited.

[0043] The sponge obtained is sliced ​​to a desired thickness, and then at least one side of the sponge is laminated with a jersey cloth made of polyester or nylon fibers to form a wetsuit fabric, which is then sewn into a wetsuit. To improve the reliability of wetsuits, materials with excellent tear strength, shrinkage, and appearance are required.

[0044] A wetsuit using the foamed rubber composition of the present invention has higher tear strength, smaller shrinkage rate and better appearance than a wetsuit using a conventional sulfur-modified chloroprene rubber. EXAMPLES

[0045] The present invention will be described in more detail below with reference to examples. Note that the examples described below are representative examples of the present invention, and the scope of the present invention should not be construed as being narrowed by these examples.

[0046] <Example 1> <Sulfur-modified chloroprene rubber> In a polymerization vessel having an internal volume of 30 liters, 100 parts by mass of chloroprene, 0.55 parts by mass of sulfur, 120 parts by mass of pure water, 4.00 parts by mass of disproportionated potassium rosinate (manufactured by Harima Chemicals Co., Ltd.), 0.60 parts by mass of sodium hydroxide, and 0.6 parts by mass of sodium salt of β-naphthalenesulfonic acid formalin condensate (trade name Demol N: manufactured by Kao Corporation) were added. The pH of the emulsion before the start of polymerization was 12.8. 0.1 parts by mass of potassium persulfate was added as a polymerization initiator, and polymerization was carried out under a nitrogen gas flow at a polymerization temperature of 40°C. When the conversion rate reached 85%, the polymerization was stopped by adding diethylhydroxyamine as a polymerization terminator, and a chloroprene polymerization liquid was obtained.

[0047] To the obtained polymerization liquid, 5 parts by mass of chloroprene as a solvent, 1 part by mass of N-cyclohexyl-2-benzothiazolesulfenamide (trade name "Noccela CZ" manufactured by Ouchi Shinko Chemical Industry Co., Ltd.) and 1 part by mass of 2-mercaptobenzimidazole (trade name "Nocrac MB" manufactured by Ouchi Shinko Chemical Industry Co., Ltd.) as molecular weight regulators, 0.05 parts by mass of sodium salt of β-naphthalenesulfonic acid formalin condensate as a dispersant, and 0.05 parts by mass of sodium lauryl sulfate as an emulsifier were added to obtain a sulfur-modified chloroprene polymer latex before molecular weight adjustment.

[0048] The obtained sulfur-modified chloroprene polymer latex was distilled under reduced pressure to remove unreacted monomers, and the mixture was kept at a temperature of 50°C for 1 hour with stirring to adjust the molecular weight, thereby obtaining a latex after molecular weight adjustment (hereinafter, this latex after molecular weight adjustment is abbreviated as "latex").

[0049] The obtained latex was cooled, and the polymer was isolated by a conventional freezing-coagulation method to obtain a sulfur-modified chloroprene rubber. The functional groups of the obtained sulfur-modified chloroprene rubber were 0.15 parts by mass of functional group A derived from N-cyclohexyl-2-benzothiazole sulfenamide represented by chemical formula 1 and 0.13 parts by mass of functional group B derived from 2-mercaptobenzimidazole represented by chemical formula 2, relative to 100 parts by mass of the sulfur-modified chloroprene rubber. [ka] [ka]

[0050] <Measurement of Mooney Viscosity> The sulfur-modified chloroprene rubber (raw rubber) obtained above was subjected to Mooney viscosity measurement in accordance with JIS K 6300-1, with an L-type rotor preheating time of 1 minute, a rotation time of 4 minutes, and a test temperature of 100°C.

[0051] <Preparation of samples for evaluation> The sulfur-modified chloroprene rubber obtained above and the compounds shown in Table 1 were mixed using an 8-inch roll, and the resulting unvulcanized compound was press-vulcanized twice to produce a sponge in accordance with JIS K 6299. The first press vulcanization is called the primary vulcanization, and the second press vulcanization is called the secondary vulcanization.

[0052] The primary vulcanization was carried out by placing 102g of unvulcanized compound (filling rate 105%) into a mold with a cavity area of ​​100mm length, 95mm width, and 8mm height, and heating the cavity area to a pressure of 3.5MPa or more and 145°C for 20 minutes. It was then left to stand for 10 minutes under atmospheric pressure and 23°C. The primary vulcanized compound obtained after standing was placed into a mold with a cavity area of ​​175mm length, 170mm width, and 16mm height, and heating the cavity area to a pressure of 3.5MPa or more and 155°C for 20 minutes.

[0053] The compounds listed in Table 1 are as follows: Lubricant / processing aid 1: Stearic acid 50S manufactured by New Japan Chemical Co., Ltd. Lubricant / processing aid 2: Struktol WB212 manufactured by S&S Japan Co., Ltd. Anti-aging agent 1: Nocrac AD-F manufactured by Ouchi Shinko Chemical Industry Co., Ltd. Anti-aging agent 2: Nocrac NBC manufactured by Ouchi Shinko Chemical Industry Co., Ltd. Magnesium oxide: Kyowamag 150 manufactured by Kyowa Chemical Industry Co., Ltd. Carbon black: Asahi Thermal manufactured by Asahi Carbon Co., Ltd. Filler 1: Dexyclay manufactured by Shiraishi Calcium Co., Ltd. Filler 2: Crown clay manufactured by Shiraishi Calcium Co., Ltd. Plasticizer 1: Naphthenic mineral oil NP-24 manufactured by Idemitsu Kosan Co., Ltd. Plasticizer 2: Aromatic process oil AH-16 manufactured by Idemitsu Kosan Co., Ltd. Wax: Paraffin wax 130°F manufactured by Nippon Seiro Co., Ltd. Vulcanizing agent: Sakai Chemical Industry Co., Ltd. Zinc oxide type 2 Foaming agent 1: Cellmic S (p,p'-oxybisbenzenesulfonyl hydrazide) manufactured by Sankyo Kasei Co., Ltd.

[0054] <Examples 2 to 7 and Comparative Examples 1 to 3> A sulfur-modified chloroprene rubber was obtained in the same manner as in Example 1, except that the amount of the molecular weight modifier added was adjusted and the contents of the functional group and the molecular weight modifier were changed.

[0055] <Example 8> An evaluation sample was prepared in the same manner as in Example 1, except that a sulfur-modified chloroprene rubber obtained by changing the amount of N-cyclohexyl-2-benzothiazole sulfenamide added for molecular weight adjustment from 1 part by mass to 0.3 parts by mass and changing the treatment time of the molecular weight adjustment process from 1 hour to 3 hours was used.

[0056] <Example 9> An evaluation sample was prepared in the same manner as in Example 1, except that a sulfur-modified chloroprene rubber obtained by changing the amount of the molecular weight regulator, N-cyclohexyl-2-benzothiazole sulfenamide, added from 1 part by mass to 1.5 parts by mass and changing the treatment time of the molecular weight adjustment process from 1 hour to 15 minutes was used.

[0057] <Example 10> An evaluation sample was prepared in the same manner as in Example 1, except that a sulfur-modified chloroprene rubber was used in which the amount of the molecular weight regulator, 2-mercaptobenzimidazole, added was changed from 1 part by mass to 1.5 parts by mass, and the processing time of the molecular weight adjustment process was changed from 1 hour to 15 minutes.

[0058] <Example 11> A sulfur-modified chloroprene rubber was obtained in the same manner as in Example 1, except that the amount of the molecular weight regulator, 2-mercaptobenzimidazole, added was changed from 4 parts by mass to 8 parts by mass, and the processing time of the molecular weight adjustment step was changed from 1 hour to 15 minutes.

[0059] <Example 12> An evaluation sample was prepared in the same manner as in Example 1, except that a sulfur-modified chloroprene rubber obtained by changing N-cyclohexyl-2-benzothiazole sulfenamide to N-cyclohexyl-4-methyl-2-benzothiazole sulfenamide (manufactured by Chemieliva Pharma & Chem Co., LTD) was used as the molecular weight modifier. The functional groups of the obtained sulfur-modified chloroprene rubber were 0.17 parts by mass of imidazole terminal species A derived from 2-mercaptobenzimidazole represented by the above chemical formula 2, and 0.15 parts by mass of thiazole terminal species B derived from N-cyclohexyl-4-methyl-2-benzothiazole sulfenamide represented by the chemical formula 3. [ka]

[0060] <Example 13> An evaluation sample was prepared in the same manner as in Example 1, except that a sulfur-modified chloroprene rubber obtained by changing 2-mercaptobenzimidazole to 2-mercapto-5-carboxybenzimidazole (trade name "2MB5C" manufactured by Kawaguchi Chemical Industry Co., Ltd.) was used as the molecular weight modifier. The functional groups of the obtained sulfur-modified chloroprene rubber were 0.16 parts by mass of thiazole terminal species A derived from N-cyclohexyl-2-benzothiazole sulfenamide represented by the above chemical formula 1, and 0.13 parts by mass of imidazole terminal species B derived from 2-mercapto-5-carboxybenzimidazole represented by chemical formula 4. [ka]

[0061] <Example 14> An evaluation sample was prepared in the same manner as in Example 1, except that a sulfur-modified chloroprene rubber obtained by changing the molecular weight modifier from N-cyclohexyl-2-benzothiazole sulfenamide to N-cyclohexyl-4-methyl-2-benzothiazole sulfenamide and from 2-mercaptobenzimidazole to 2-mercapto-5-carboxybenzimidazole was used. The functional groups of the obtained sulfur-modified chloroprene rubber were 0.14 parts by mass of thiazole terminal species B derived from N-cyclohexyl-4-methyl-2-benzothiazole sulfenamide represented by the above chemical formula 3, and 0.16 parts by mass of imidazole terminal species B derived from 2-mercapto-5-carboxybenzimidazole represented by the above chemical formula 4.

[0062] <Example 15> An evaluation sample was prepared in the same manner as in Example 1, except that Foaming Agent 1 was changed to Foaming Agent 2 (product name "Cellmike C", azodicarbonamide manufactured by Sankyo Kasei Co., Ltd.) and the amount added was changed to 5 parts by mass.

[0063] <Example 16> An evaluation sample was prepared in the same manner as in Example 1, except that the amount of foaming agent 1 added was 4 parts by mass and the amount of foaming agent 2 added was 2.5 parts by mass.

[0064] <Comparative Example 4> An evaluation sample was prepared in the same manner as in Example 1, except that the molecular weight modifier was changed from N-cyclohexyl-2-benzothiazole sulfenamide and 2-mercaptobenzimidazole to tetraethylthiuram disulfide (product name "Noccela TET" manufactured by Ouchi Shinko Chemical Industry Co., Ltd.) and the amount of the added agent was changed to 2.5 parts by mass to obtain a sulfur-modified chloroprene rubber. The functional group of the obtained sulfur-modified chloroprene rubber was 0.26 parts by mass of the functional group derived from tetraethylthiuram disulfide represented by chemical formula 5. [ka]

[0065] <Comparative Example 5> An evaluation sample was prepared in the same manner as in Example 1, except that the amount of the foaming agent 1 added was changed from 8 parts by mass to 2 parts by mass.

[0066] <Comparative Example 6> An evaluation sample was prepared in the same manner as in Example 1, except that the amount of the foaming agent 1 added was changed from 8 parts by mass to 20 parts by mass.

[0067] <Evaluation of tear strength> The obtained sponge was cut into No. 4 angle-shaped test pieces without notches using a punching tool in accordance with JIS K 6400-1, and then measured at a test speed of 500 mm / min using a constant-speed tensile tester in accordance with JIS K6400-5. The maximum tear load shown until the test piece broke was divided by the film thickness to determine the tear strength.

[0068] <Evaluation of shrinkage rate> The obtained sponge was left to stand for 168 hours under atmospheric pressure and 23°C, and then the surface layer of the sponge was sliced ​​to a thickness of 2 mm ± 0.20 mm to produce a sponge sheet. The length and width of the sponge sheet immediately after slicing were measured as a reference, and then the length and width of the sponge sheet was measured again after leaving it to stand for 168 hours under atmospheric pressure and 23°C. The shrinkage rate was calculated using the following formula, where the length of the sponge sheet immediately after slicing is H0 (mm), the width is L0 (mm), and the length of the sponge sheet after leaving it to stand for 168 hours is H1 (mm), and the width is L1 (mm). Shrinkage rate (%) = (H0 x L0 - H1 x L1) ÷ (H0 x L0) x 100

[0069] <Appearance evaluation> The sponge thus obtained was left to stand at atmospheric pressure at 23°C for 24 hours, after which the surface condition was visually observed. Observation was performed for the following three items, with samples that were rated as ○ in all items being rated as ○, and samples that were not rated as ○ in any items being rated as △. Item 1 Presence or absence of craters The presence or absence of crater-like irregularities caused by gas leakage, etc. was confirmed. Those that were not observed at all were marked with ○. Item 2 Presence or absence of claw marks The surface of the sponge was lightly pressed with a fingernail and then the presence or absence of a nail mark was observed when the sponge was released. Those that did not remain at all were marked as ○. Item 3 Observation of corners Wrinkles due to shrinkage were observed at the corners of the sponge. Those in which the corners remained firmly attached were marked as ○.

[0070] <Result> The results of the Examples are shown in Tables 1 and 2 below, and the results of the Comparative Examples are shown in Table 3 below.

[0071] [Table 1]

[0072] [Table 2]

[0073] [Table 3]

[0074] As shown in Tables 1 and 2, it was confirmed that the evaluation samples of Examples 1 to 16 provided molded articles with excellent tear strength, shrinkage rate, and appearance. The Mooney viscosity of Comparative Example 1 was too low to prepare an evaluation sample. The foam of Comparative Example 5 did not foam, and an evaluation sample could not be prepared.

Claims

1. A foamed rubber composition comprising: 100 parts by mass of a sulfur-modified chloroprene rubber having, at a molecular end, a functional group A represented by the following general formula (A) and a functional group B represented by the following general formula (B), wherein a mass ratio B / A of a content (B) of the functional group B to a content (A) of the functional group A is more than 0 and is 6.0 or less, and a total content of the functional group A and the functional group B is 0.10 to 0.60 parts by mass; and 3 to 16 parts by mass of a chemical foaming agent. 【Chemistry 1】 (In the formula, R 1 , R 2 each independently represents a hydrogen atom, a halogen atom, a hydroxyl group, a cyano group, an alkyl group which may have a substituent, or an arylthio group which may have a substituent; R 1 , R 2 may be bonded to each other to form a ring which may have a substituent.) 【Chemistry 2】 (In the formula, R 3 , R 4 each independently represents a hydrogen atom, a halogen atom, a hydroxyl group, a cyano group, an alkyl group which may have a substituent, or an arylthio group which may have a substituent; R 3 , R 4 may be bonded to each other to form a ring which may have a substituent.)

2. The functional group A is R 1 and R 2 The foamed rubber composition according to claim 1 , wherein the benzothiazole rings are formed by bonding to each other.

3. The functional group B is R 3 and R 4 The foamed rubber composition according to claim 1 or 2, wherein the benzimidazole rings are formed by bonding to each other.

4. The foamed rubber composition according to any one of claims 1 to 3, comprising 0.05 to 0.40 parts by mass of the functional group A relative to 100 parts by mass of the sulfur-modified chloroprene.

5. The foamed rubber composition according to any one of claims 1 to 4, comprising 0.05 to 0.40 parts by mass of the functional group B relative to 100 parts by mass of the sulfur-modified chloroprene.

6. The foamed rubber composition according to any one of claims 1 to 5, comprising 0.0005 to 0.01 parts by mass of thiazole per 100 parts by mass of the sulfur-modified chloroprene rubber.

7. The thiazole is N-cyclohexyl-2-benzothiazole sulfenamide, N-cyclohexyl-4-methyl-2-benzothiazole sulfenamide, N-cyclohexyl-4,5-dimethyl-2-benzothiazole sulfenamide, N,N-dicyclohexyl-1,3-benzothiazole-2-sulfenamide, N-(tert-butyl)-2-benzothiazole sulfenamide, N,N-diisopropyl-2-benzothiazole sulfenamide, 4,5-dihydro The foamed rubber composition according to claim 6, which is at least one compound selected from the group consisting of thiazole-2-sulfenamide, N-cyclohexyl-4,5-dihydrothiazole-2-sulfenamide, N-oxydiethylbenzothiazole-2-sulfenamide, 2-(4'-morpholinyldithio)benzothiazole, 2-mercaptobenzothiazole, 4,5-dihydro-2-mercaptothiazole, dibenzylthiazolyl disulfide, and 2-(morpholinodithio)benzothiazole.

8. The composition contains 0.005 to 0.2 parts by mass of an imidazole relative to 100 parts by mass of the sulfur-modified chloroprene rubber, The foamed rubber composition according to claim 6 or 7, wherein the imidazoles are at least one compound selected from the group consisting of 2-mercaptoimidazole, 2-mercaptobenzimidazole, N-cyclohexyl-1H-benzimidazole-2-sulfenamide, 2-mercaptomethylbenzimidazole, 2-mercapto-5-methoxybenzimidazole, 2-mercapto-5-carboxybenzimidazole, sodium 2-mercaptobenzimidazole-5-sulfonate dihydrate, 2-mercapto-5-nitrobenzimidazole, and 2-mercapto-5-aminobenzimidazole.

9. The foamed rubber composition according to claim 8, wherein a mass ratio D / C of a content D of the imidazoles to a content C of the thiazole is 0 to 200.

10. The foamed rubber composition according to any one of claims 1 to 9, wherein the sulfur-modified chloroprene rubber has a Mooney viscosity of 20 to 80.

11. The foamed rubber composition according to any one of claims 1 to 10, wherein the chemical foaming agent is at least one selected from the group consisting of an azo compound, a nitroso compound, a sulfonyl hydrazide compound, an azide compound, and an inorganic foaming agent.

12. A sponge comprising the foamed rubber composition according to any one of claims 1 to 11.

13. A molded article comprising the sponge according to claim 12.

Citation Information

Patent Citations

  • Chloroprene rubber composition for highly expanded sponge vulcanized by non-pressure open process

    JP1998298328A

  • Chloroprene rubber foam and method for producing the same

    JP2012067235A

  • Rubber composition, vulcanizate of the rubber composition, and molding

    JP2021031526A

  • Rubber composition, and vulcanizate and molding of rubber composition

    JP2021172695A

  • Sulfur-modified chloroprene rubber composition, vulcanized product, molded article using said vulcanized product and method for producing sulfur-modified chloroprene rubber composition

    WO2019102898A1